PKM Pelatiahan Pemanfaatan Sampah Organik sebagai Pupuk Kompos Ramah Lingkungan dikawasan Wisata Alam Puntodo - Nurhayani H. Muhiddin; Sitti Saenab; Irwandi Rahmat; Ahmad Syakur; Salma Samputri (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2024)
Natural tourism areas are places that prioritize the potential of natural resources as tourism objects, both in their natural state and after cultivation efforts. However, apart from its aesthetic and economic benefits, tourist areas also have several problems, one of the problems is an environmental problem. One of the famous natural attractions in the South Sulawesi area is the protection and management of the Puntondo environment. The aim of this community service activity is that through outreach and training activities it is hoped that it will be able to increase the knowledge and skills of the community, both peoples who living in the PPLH Puntondo area and around the PPLH Puntondo area regarding processing organic waste or food waste into compost. The activity began with a presentation through socialization of material about organic waste and compost fertilizer in general, then continued with a short simulation and introduction to tools and materials for making compost fertilizer from organic waste. The compost making process is carried out in a 20 L composter using EM-4 bioactivator. The results obtained from this community service activity are an increase in the knowledge and skills of the community in the Puntondo PPLH area regarding processing organic waste into compost.